Spermicide of Papaya Seed Oil and Compounds - I Made Sukadana; Sri Rahayu Santi; Ni Putu Lisna Oktaviani (Bogor Agricultural University, Indonesia, 2023)
This study aimed to determine the spermicidal activity of papaya seed oil (Carica papaya L) from local Bali varieties against Wistar rat spermatozoa by evaluating sperm quality and the correlation between the percentage of motility and viability spermatozoa to identify its active compounds. Papaya seed oil was obtained by extracting papaya seeds using n-hexane solvent. The study was designed as follows; group of spermatozoa Wistar rat were treated with NaCl 0.9% (control, P0), with Sodium carboxy methyl cellulose (NaCMC) 0.5% (P1), with n-hexane extract 0.1%(b/v) (P2), with n-hexane extract 0.3%(b/v) (P3), and with n-hexane extract 0.5%(b/v) (P4). Column chromatography was used to separate the n-hexane extract into two fractions, A and B. The spermicide test for fractions A and B followed the same design as the test for n-hexane extract but until the P7 group. The result showed that fraction B exhibited higher spermicidal activity, with 23.3% motility and 33.8% of viability sperm at 100 ppm. The identification of fraction B by LCMS showed at least 12 mixture compounds were venoterpine, vitamin K5, 5-phenyl-2-pyridinamine, harmalan, styrylquinoline, 1,2,3,4-tetrahydro-1-benzoyl-2-methyl-4-phenylamino-quinoline, calcitroic acid, siderol, N-benzyl-linoleamide, (3Î²)-3-(diisopropylamino)androst-5-en-17-one, pipereicosalidine, and 25-azacholesterol. Spermicidal activity may be a synergistic effect of several compounds that have a cytotoxic activity such as styrylquinoline, 1,2,3,4-tetrahydro-1-benzoyl-2-methyl-4-phenylamino-quinoline, siderol, and pipereicosalidine.